Wreath of forget-me-nots. Postures of Czech women authors in the 1840s - Kateřina Piorecká (Slovenska Literatura, 2023)
The idea of the woman writer in the Czech literary field of the first half of the 19th century was informed by the male mystifications of Czech women writers. In literary communication, their creators modelled female writers who never existed, invented their life stories and attributed to them the qualities they believed Czech women writers should possess. The first Czech circle of women patriots and writers then had to cope with this legacy. They used a variety of strategies to make their way: their debut collections of poems would refer to their fictional predecessors, they would work on the Czech encyclopaedia, combine writing with educational work, or smoke in public – the last of which was supposed to give the Czech author a George Sandian worldliness. To analyse their positions in the literary field of the first half of the 19th century, I use the term posture, which, following Alain Viala, the Swiss scholar Jérôme Meizoz understands as a unique way of taking a position in the literary field. In the context of history and language, the term posture has two dimensions: it is simultaneously defined as an act and as a discourse. On the one hand, it refers to self-representations within public discourses in literary situations, and on the other hand, it refers to the image itself given through discourse, which rhetoric refers to as ethos.